Senescent cells suppress macrophage-mediated corpse removal via upregulation of the CD47-QPCT/L axis - Schloesser, Daniela; Lindenthal, Laura; Sauer, Julia; Chung, Kyoung-Jin; Chavakis, Triantafyllos; Griesser, Eva; Baskaran, Praveen; Maier-Habelsberger, Ulrike; Fundel-Clemens, Katrin; Schlotthauer, Ines; Watson, Carolin Kirsten; Swee, Lee Kim; et al. (The Journal of cell biology, 2023)
Progressive accrual of senescent cells in aging and chronic diseases is associated with detrimental effects in tissue homeostasis. We found that senescent fibroblasts and epithelia were not only refractory to macrophage-mediated engulfment and removal, but they also paralyzed the ability of macrophages to remove bystander apoptotic corpses. Senescent cell-mediated efferocytosis suppression (SCES) was independent of the senescence-associated secretory phenotype (SASP) but instead required direct contact between macrophages and senescent cells. SCES involved augmented senescent cell expression of CD47 coinciding with increased CD47-modifying enzymes QPCT/L. SCES was reversible by interfering with the SIRPα-CD47-SHP-1 axis or QPCT/L activity. While CD47 expression increased in human and mouse senescent cells in vitro and in vivo, another ITIM-containing protein, CD24, contributed to SCES specifically in human epithelial senescent cells where it compensated for genetic deficiency in CD47. Thus, CD47 and CD24 link the pathogenic effects of senescent cells to homeostatic macrophage functions, such as efferocytosis, which we hypothesize must occur efficiently to maintain tissue homeostasis.